Adjuvantes: impacto na eficácia de vacina de subunidade contra leptospirose - Bacelo, Kátia Leston (2013)
A major challenge for the development of vaccines based on purified or recombinant protein subunits, and synthetic peptides resides in the fact that these are poorly immunogenic and mobilize insufficient immunoprotective response. Adjuvants are often used in association with these subunits in order to amplify and direct the immune response induced. Nowadays, there is a wide range of compounds that demonstrate adjuvant activity, however, few are approved for human use, and these often fail to induce appropriate immune response against a particular pathogen. Thus, there is a need to develop new adjuvants that are safe, effective and represent an alternative to currently available. In the present study, we used as a model antigen the non- identical portion of the Leptospira LigA protein (Leptospiral immunoglobulin-like protein A), an outer membrane protein of great interest as a mediator pathogenic mechanisms, used in serological diagnosis and as experimental vaccines. This antigen was formulated with various adjuvants, and the formulations tested for their immunoprotective potential in hamsters, challenged with a virulent strain of L. interrogans serovar Copenhageni. For this, the LigAni protein was produced in recombinant form (rLigAni) using Escherichia coli as the expression system and associated to xanthan polysaccharide, in its variants xanthan pruni strains 106 (X1) and 101 (X2), commercial xanthan and also to oligodinucleotídeo CpG (CpG ODN), carbon nanotubes (CNTs) and aluminum hydroxide (Alhydrogel). Formulations containing rLigAni associated with xanthan polysaccharide and CNTs induced significant IgG antibody titers, comparable to that induced when the protein was associated with Alhydrogel. Protection against lethal challenge was observed in 100%, 100%, 67% and 50% of the hamsters immunized with rLigAni-X1, rLigAni- CpG-X1, rLigAni-Alhydrogel and rLigAni-X2, respectively (Fisher test P < 0.05). The preparations containing rLigAni associated with CNTs, although induced an antibody response, failed to confer immunoprotection. Additionally, xanthan and CNTs adjuvants were not toxic to Chinese hamster ovary (CHO) cells, in vitro. The results of this study indicate xanthan as a new adjuvant for subunit vaccines against leptospirosis, presenting the ability to potentiate the immune response against the antigen, besides biocompatibility and the possibility of reduction of number of doses required for protection.